High-level dietary cadmium exposure is associated with global DNA hypermethylation in the gastropod hepatopancreas. - Dragos V Nica; Cristina Popescu; George A Draghici; Florina-Maria Andrica; Ionela A Privistirescu; Iosif I Gergen; Reinhard Stöger (PLoS ONE)
5-methylcytosine (5mC) is a key epigenetic mark which influences gene expression and phenotype. In vertebrates, this epigenetic mark is sensitive to Cd exposure, but there is no information linking such an event with changes in global 5mC levels in terrestrial gastropods despite their importance as excellentecotoxicological bioindicators of metal contamination. Therefore, we first evaluated total 5mC content in DNA of the hepatopancreas of adult Cantareus aspersus with the aim to determine whether this epigenetic mark is responsive to Cd exposure. The experiment was conducted under laboratory conditions and involved a continuous exposure, multiple dose- and time-point (14, 28, and 56 days) study design. Hepatopancreas cadmium levels were measured using Flame Atomic Absorption Spectrometry and the percentage of 5-mC in samples using an ELISA-based colorimetric assay. Snail death rates were also assessed. Our results, for the first time, reveal the presence of 5mC in C. aspersus and provide evidence for Cd-induced changes in global 5mC levels in DNA of gastropods and mollusks. Although less sensitive than tissue accumulation, DNA methylation levels responded in a dose- and time-dependent manner to dietary cadmium, with exposure dose having a much stronger effect than exposure duration. An obvious trend of increasing 5mC levels was observed starting at 28 days of exposure to the second highest dose and this trend persisted at the two highest treatments for close to one month, when the experiment was terminated after 56 days. Moreover, a strong association was identified between Cd concentrations in the hepatopancreas and DNA methylation levels in this organ. These data indicate an overall trend towards DNA hypermethylation with elevated Cd exposure. No consistent lethal effect was observed, irrespective of time point and Cd-dosage. Overall, our findings suggest that the total 5mC content in DNA of the hepatopancreas of land snails is responsive to sublethal Cd exposure and give new insights into invertebrate environmental epigenetics.